Development Of Karawitan Arts And Creation Of Welcome Dance In Madenan Village | Pembinaan Seni Karawitan Dan Penciptaan Iringan Tari Penyambutan Di Desa Madenan - Navio Gede Navio Raykin; I Nyoman Kariasa (Pusat Penerbitan LPPMPP ISI Denpasar, 2024)
This article contains about Freedom to Learn on an Independent Campus in the Thematic Real Work Lecture (KKNT) program which was held in Madenan Village, Tejakula District, Buleleng Regency. The purpose of this KKNT is to develop Madenan Village through karawitan art and provide experience to the author in applying theoretical knowledge and developing the practice of learning and creating karawitan art in the community. The entire work program is carried out using data collection methods, namely observation, interviews, documentation or library research. In the creation of the gending method used is Panca Sthiti Ngawi Sani which has been tested in the creation of art. During the process of implementing the Thematic Real Work Lecture, several pieces were produced, namely in Gong Kebyar drawing two percussion, namely Telu Buaya Mangap and Sekatian Ririg Cenik, in Gamelan Gender Wayang performing two percussion, namely Seketi and Rebong. The musical dance of the Madenan Village mascot in the form of a welcoming dance is entitled “Kiraja” inspired by the very unique durian fruit that only exists in Madenan Village. The success of this KKNT is the author's hope that it can continue to inspire the enthusiasm of the community and the younger generation in the arts, especially musical arts in Madenan Village.